Krisis pada Quarter-life, Peran Dukungan Sosial dalam Membantu melewatinya - Amelia Dwi Rahmah; Ulfa Masfufah (Flourishing Journal, 2023)
Humans face a variety of challenges and developmental journeys in every phase of life, including the emerging adulthood phase or at 18-25 years old, in which individuals build relationships, commit themselves to life's goals, and develop themselves. The shift from adolescence to adulthood frequently gives rise to doubt and unease, leading to a period of uncertainty known as a quarter-life crisis. This article aims to explore the role of social support from various sources affecting individuals who are experiencing quarter-life crises during the emerging adulthood phase. The research method used in the study of literature examines 10 journal articles that are relevant to the author's research. The data used in this research is secondary data, which is a type of data obtained indirectly. The data obtained was analyzed descriptively and thematically to describe findings in the literature and to identify key themes as well as relationships between information. The results show that the social support role of family, peers, and surroundings has a positive impact on reducing the rate of quarter-life crises in individuals between the ages of 18 and early 30 years. AbstrakManusia menghadapi berbagai tantangan dan perjalanan perkembangan dalam setiap fase kehidupan, termasuk dalam tahap emerging adulthood, dimana individu menjalin hubungan, berkomitmen pada tujuan hidup, dan mengembangkan diri. Peralihan dari remaja ke dewasa seringkali menimbulkan ketidakpastian dan kecemasan, memuncak dalam krisis pada quarter-life. Krisis ini dipicu oleh tuntutan dan tanggung jawab peralihan, serta tekanan sosial. Artikel ini bertujuan untuk mengeksplorasi peran dukungan sosial sehingga mampu memengaruhi individu yang sedang mengalami krisis pada quarter-life selama tahap emerging adulthood. Metode penelitian yang digunakan berupa studi literatur menelaah 10 artikel jurnal yang relevan dengan kata kunci. Data yang digunakan dalam penelitian ini adalah data sekunder, merupakan jenis data yang diperoleh secara tidak langsung. Data yang diperoleh dianalisis secara deskriptif dan tematik untuk menggambarkan temuan dalam literatur dan mengidentifikasi tema-tema utama serta hubungan antar informasi. Berdasarkan hasil penelitian dapat diamati bahwa adanya peran dukungan sosial dari keluarga, teman sebaya, dan lingkungan sekitar memiliki pengaruh positif dalam mengurangi tingkat krisis pada quarter-life pada individu yang berusia antara 18 hingga awal 30 tahun.